India in International Level (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
India is  having its own  role in the international  level and it is  it is contributing its role to world peace. As a biggest democratic nation,  India is  having its own  prestigious role in the international level.Being  a peaceful nation,  India had got the independence by  using the weapons like truth and non-violence. Its freedom movement can be termed as bloodless revolution. It means without bloodshed, it  has attained its independence and it  had given the message of peace to the other nations.Being a  peace loving nation,  it is a member of U.N.O, SAARC, ASEAN, COMMONWEALTH  group of NATIONS,  it is contributing to the world peace.Adopting the modern economy, it is adopted globalization,  privatization,  as a member of GATT agreement rtc it  is considered as a fastly   developing nation .AS a second biggest democratic nation,  it is spreading the democratic values in the world.  As a strong supporter of the U.N.O  it is providing its military  forces as peace keeping  army to contribute to the world peace.As an  independent and sovereignty nation, it  encouraged the African can  nations, to get freedom and strongly opposed colonialism.IN this paper, we are explain and presenting the terms as a role of India in the international level.